Compliance of Medical Personnel Against the Implementation of Informed Consent: A Lawsuit Prevention Study for Medical Disputes - Etyn Ariyani Susilowati; Wardah Yuspin; Absori Absori (Universitas Katolik Soegijapranata Semarang, 2021)
Abstract: Humans are social creatures, namely creatures that require interaction with other humans. Interaction between humans is not only communication but involves all aspects of life, including the legal aspect. Based on law number 36 of 2014 concerning health workers, it is anyone who devotes himself to the health sector and has knowledge and/or skills through education in the health sector which for certain types requires the authority to carry out health efforts. The purpose of this study was to determine the level of compliance of medical personnel in the implementation of informed consent. In addition, medical personnel understand the role of informed consent in preventing lawsuits and medical disputes. The research method used is a non-doctrinal research method, namely the questionnaire method, direct interviews with medical personnel, and medical record documents, especially informed consent sheets. Problem formulation: 1. How is the compliance of medical personnel with the implementation of informed consent? 2. What is the role of Informed Consent in Medical Dispute Prevention efforts? 3. What is the concept of implementing informed consent in order to prevent medical disputes? The results of the study: